SEJARAH KONFLIK KEBANGKITAN ISLAM DI MINANGKABAU: Sebuah Tinjauan Awal Terhadap Proses Kemunculannya - Ihsan Sanusi (Program Studi Sejarah Peradaban Islam Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2018)
This article in principle wants to examine the history of the emergence of the conflict of Islamic revival in Minangkabau starting from the Paderi Movement to the Youth in Minangkabau. Especially in the initial period, namely the Padri movement, there was a tragedy of violence (radicalism) that accompanied it. This study becomes important, because after all the reformation of Islam began to be realized by reforming human life in the world. Both in terms of thought with the effort to restore the correct understanding of religion as it should, from the side of the practice of religion, namely by reforming deviant practices and adapted to the instructions of the religious texts (al-Qur'an and sunnah), and also from the side of strengthening power religion. In this case the research will be directed to the efforts of renewal by the Padri to the Youth towards the Islamic community in Minangkabau. To discuss this problem used historical research methods. Through this method, it is tested and analyzed critically the records and relics of the past. In analyzing the data in this research basically used approach or interactive analysis model by Miles and Huberman. In this analysis model, the three components of the analysis are data reduction, data presentation, and conclusion drawing or verification, the activity is carried out in an interactive form with the process of collecting data as a process that continues, repeats, and continues to form acycle.